Outdoor Education in Italian Kindergartens: How Teachers Perceive Child Developmental Trajectories - Agostini, Francesca; Minelli, Marianna; Mandolesi, Roberta (Frontiers in Psychology, 2018)
Outdoor Education (OE) refers to organized experiential education that takes place in the outdoor, characterized by action-centered and thematic learning processes. Literature shows how OE may have beneficial effects on different areas of child development, including cognitive abilities, social skills, and motor development. This relationship is not necessarily linear, but moderated by different variables. Until now, few studies have examined, using rigorous methods, the role of OE in children's development and studies of preschool aged children remain lacking. The current study aimed to explore teachers' perceptions of children's developmental trajectories over 2 school years, investigating whether teachers' perceptions differed between two kindergartens, one characterized by a consolidated OE approach and the other one characterized by a more traditional method of education. The sample was composed of 20 teachers, evaluating 93 children aged 3–5 (M = 46.95 months, SD = 6.73; 42 males): 13 teachers were from a traditional kindergarten (Traditional Group- TG) and evaluated 52 children; 7 teachers were from an OE kindergarten (Outdoor Group—OE) and observed 41 children. All the teachers completed the Kuno Beller Developmental Tables (Mantovani, 1995), in order to describe specific child developmental areas in 4 consecutive moments during 2 school years (T1-T2: January-May 2014; T3-T4: October 2014-May 2015). The 20 teachers also completed the “Outdoor Activities/Trips Diary,” an instrument created for this study to collect qualitative data on the characteristics of outdoor activities. Results showed that, in all the developmental areas, OE teachers perceived higher scores over time were found for the Outdoor Group compared to the Traditional one. Specifically, GLM ANOVAs Repeated Measures revealed a significant interaction of the 2 variables Time and Groups (p < 0.001): contrast analyses showed that OE children, compared to the TG children, were perceived by their teachers with higher levels in all developmental areas at T1 and T2, but not at T3 and T4. The findings suggest that the OE activites, compared to indoor ones and according to teachers' perceptions, offer greater opportunities to promote the child's development at different levels, especially when children are younger. Future studies are recommended analyzing possible moderating variables and long term effects of OE.